Cryptotanshinone Attenuates Oxygen-Glucose Deprivation/ Recovery-Induced Injury in an in vitro Model of Neurovascular Unit - Zhao, Hongye; Zheng, Tiezheng; Yang, Xiaohan; Fan, Ming; Zhu, Lingling; Liu, Shuhong; Wu, Liying; Sun, Changkai (Frontiers in Neurology, 2019)
Cryptotanshinone (CTs), an active component isolated from the root of Salvia miltiorrhiza, has been demonstrated to be effective for both myocardial and hepatic ischemia/reperfusion damage. We here established an oxygen-glucose deprivation/recovery (OGD/R) model of Neurovascular Unit (NVU) in vitro to observe the effects of CTs on cerebral ischemia/reperfusion injury (CIRI), and explore the underlying mechanisms. CTs was observed to significantly inhibit the OGD/R-induced neuronal apoptosis, and reduce the activation of Caspase-3 and poly (ADP-ribose) polymerase (PARP), as well as the increase of Bax/Bcl-2 ratio in neurons under OGD/R condition. The inhibitory effects of CTs on neuron apoptosis were associated with the blocking of the JNK and p38 MAPK signaling pathway. CTs also remarkably ameliorated OGD/R-induced reduction of transepithelial membrane resistance (TEER) values and the increase of transendothelial permeability coefficient (Pe) of sodium fluorescein (SF) by enhancing the expression of ZO-1, Occludin and Claudin-5 in BMECs, which might be related to the downregulation of matrix metalloprotein (MMP)-9 expression. Altogether, our data indicate that CTs has protective effects against OGD/R injure in NVU models in vitro via the amelioration of neuronal apoptosis and BBB disrupt, suggesting that CTs is a candidate medicine for CIRI.